2019
DOI: 10.1016/j.neubiorev.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics and probiotics for depression and anxiety: A systematic review and meta-analysis of controlled clinical trials

Abstract: With growing interest in the gut microbiome, prebiotics and probiotics have received considerable attention as potential treatments for depression and anxiety. We conducted a random-effects metaanalysis of 34 controlled clinical trials evaluating the effects of prebiotics and probiotics on depression and anxiety. Prebiotics did not differ from placebo for depression (d = −.08, p = .51) or anxiety (d = .12, p = .11). Probiotics yielded small but significant effects for depression (d = −.24, p < .01) and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(248 citation statements)
references
References 72 publications
(174 reference statements)
9
200
0
13
Order By: Relevance
“…The effectiveness of probiotic administration in MD constitutes a strong evidence for developing microbiota-orientated treatments in this indication. Probiotics have yielded medium-to-large significant effects in the setting of depression (d = −0.73 (95% CI = −1.02-−0.44)) in a recent meta-analysis [51]. Approximately half of all existing studies were published over the past two years, reflecting the rapidly growing interest in this area.…”
Section: Madan Et Al 2020 [47]mentioning
confidence: 99%
“…The effectiveness of probiotic administration in MD constitutes a strong evidence for developing microbiota-orientated treatments in this indication. Probiotics have yielded medium-to-large significant effects in the setting of depression (d = −0.73 (95% CI = −1.02-−0.44)) in a recent meta-analysis [51]. Approximately half of all existing studies were published over the past two years, reflecting the rapidly growing interest in this area.…”
Section: Madan Et Al 2020 [47]mentioning
confidence: 99%
“…It should be noted that there are relatively few examples of microbiome-directed interventions that are clinic-ready in general [30,31] and harnessing our current knowledge of the microbiomegut-brain axis to improve a mental illness like depression is not without challenges. While the combined data from the preclinical studies, exploratory studies in healthy human subjects and the modulation of depression and anxiety scores is promising, a move toward the inclusion of subjects with a clinical diagnosis of depression is now warranted [32,33]. In this regard, it is well recognized that there are considerable translational obstacles to moving this research from mouse to man and we already have some attrition with examples of this failure to translate for specific psychobiotics [34] mixed in with encouraging success stories [35,36].…”
Section: Troubled Waters: Correlation To Causation Moving Towards Mementioning
confidence: 99%
“…The study of psychobiotics has shown promising results in regard to the effect of probiotics on anxiety and depression, however, this area of research is still on its infancy [112,113]. Probiotic supplementation of a single or few strains may augment the population of that speci c microbe(s) and therefore change overall gut microbial function [114].…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Probiotic supplementation of a single or few strains may augment the population of that speci c microbe(s) and therefore change overall gut microbial function [114]. This effect may be sought in patients with depressive or anxiety disorders, however, whether healthy adults can be bene ciated by the consumption of a single or few strains of probiotics is still not well understood [112]. FMT provide a wider array of microbes that have shown to reduce anxiety and depression; however, they also involve risks such as unintentional transplantation of multi-drug resistant organisms [114,115].…”
Section: Clinical Perspectivementioning
confidence: 99%